Monitoring human papillomavirus prevalence among young Australian women undergoing routine chlamydia screening. Issue 5 (29th January 2020) - Shilling, Hannah; Murray, Gerald; Brotherton, Julia M.L.; Hawkes, David; Saville, Marion; Sivertsen, Terri; Chambers, Ian; Roberts, Jennifer; Farnsworth, Annabelle; Garland, Suzanne M.; Hocking, Jane S.; Kaldor, John; et al.
Highlights: Utilising residual chlamydia specimens is a feasible method for HPV surveillance in Australia. HPV results of 362 residual specimens were matched with demographic and vaccine registry data for 98.6% We detected HPV 16/18 in 3% women, and HPV 31/33/45/52/58 in 19%; 7.8% had a positive chlamydia test. Abstract: Introduction: Australia has recently implemented major changes in cervical cancer prevention policies including introduction of primary human papillomavirus (HPV) screening starting at age 25, and replacement of the quadrivalent HPV vaccine with the nonavalent vaccine in the national school-based program. We assessed the feasibility and utility of conducting HPV testing in residual clinical specimens submitted for routine Chlamydia trachomatis screening, as a means of tracking HPV vaccine program impact among young sexually active women. Methods: De-identified residual specimens from women aged 16–24 years submitted for chlamydia testing were collected from three pathology laboratories in Victoria and New South Wales. Limited demographic information, and chlamydia test results were also collected. Patient identifiers were sent directly from the laboratories to the National HPV Vaccination Program Register, to obtain HPV vaccination histories. Samples underwent HPV genotyping using Seegene Anyplex II HPV 28 assay. Results: Between April and July 2018, 362 residual samples were collected, the majority (60.2%) of which were cervical swabs. Demographic data and vaccination histories were received for 357 (98.6%) women (mean age 21.8, SD 2.0). Overall, 65.6% of women were fully vaccinated, 9.8% partially, and 24.7% unvaccinated. The majority (86.0%) resided in a major city, 35.9% were classified in the upper quintile of socioeconomic advantage and chlamydia positivity was 7.8%. The prevalence of quadrivalent vaccine-targeted types (HPV6/11/16/18) was 2.8% (1.5–5.1%) overall with no differences by vaccination status (p = 0.729). The prevalence of additional nonavalent vaccine-targeted types (HPV31/33/45/52/58) was 19.3% (15.6–23.8%). One or more oncogenic HPV types were detected in 46.8% (95% CI 41.6–52.0%) of women. Conclusions: HPV testing of residual chlamydia specimens provides a simple, feasible method for monitoring circulating genotypes. Applied on a larger scale this method can be utilised to obtain a timely assessment of nonavalent vaccine impact among young women not yet eligible for cervical screening.